A theoretical analysis on the electron and energy transfer between host and guest materials in phosphor–doped OLED - You, Xiao-Xia; Gao, Jing; Duan, Ying-Chen; Geng, Yun; Zhang, Min; Zhao, Liang; Su, Zhong-Min (Journal of photochemistry and photobiology. A, Chemistry., 2022)
In this work about doped PHOLEDs, energy transfer between host and guest molecules were proved to play more important role in generating triplet exciton for guest material than the electron transfer in luminescent layer. [Display omitted] •A deep theoretical investigation on the charge and energy transfer processes between host and guest molecules in the phosphor-doped OLED were investigated.•Energy transfer between host and guest molecules plays more important role in generating triplet exciton for guest material than the charge transfer.•The energy transfer is less sensitive to the intermolecular relative position than the electron transfer. Phosphor doped OLEDs have been developed all the way in recent years due to their high and stable efficiency and more practical applications in various display devices. However, complicated electron and energy transfer between host and guest materials have not been clear to us so far, which brings about the difficulty in making favorable doping scheme to realize best performance. In order to present some issues for these processes, we carried out density functional theory (DFT) calculations and molecular dynamics (MD) simulation to describe the electron and energy transfer between host molecule CBP and guest molecules (ppy)2Ir(bppo), (bppo)2Ir(ppy) and (bppo)2Ir(acac). The results show that the energy transfer from host to guest molecules is not only more significant than the charge transfer, but also exhibits less dependence on the relative orientation between host and guest molecules. It indicates the decisive contribution of energy transfer to the high-efficiency phosphorescence of guest molecules. At the same time, the much higher energy transfer rates between triplet excited states than those between singlet excited states indicates the importance of generating triplet-state excitons in host materials for phosphor doped OLEDs. Therefore, we hope this work could provide some theoretical guidance for further development of host–guest materials.